Predictive value of circulating N-terminal pro-brain natriuretic peptide in patients after treatment of Hodgkin lymphoma (a 3-year prospective study) - B. B. Samura (Zaporozhye State Medical University, 2017)
We aimed to evaluate the prognostic value of circulating N-terminal pro-brain natriuretic peptide (NT-proBNP) in appearance of cardiovascular events in patients after treatment of Hodgkin lymphoma. Methods: Blood samples for biomarkers measurements were collected. ELISA method for measurements of circulating level of NT-proBNP was used. Results: During observation period progression of Hodgkin lymphoma was proved in 8 (22.2%) patients, 4 (11.1%) persons were excluded for poor follow-up. Thirty four cumulative clinical events occurred in 11 patients (30.6%) within the follow-up, with their distribution being as follows: 2 cardiovascular deaths, 16 cardiac arrhythmias, 6 cardiac ischemic events, 1 stroke, 4 chronic heart failures and 5 hospital admissions for cardiovascular reasons. 4 deaths were not related with cardiovascular pathology or cardiovascular reasons. Medians of circulating NT-proBNP levels in free-events subject cohort and subject cohort with cardiovascular events were 5.68 (2.34-7.97) pg/ml and 13.60 (4.83-17.67) pg/ml (р=0.072). The differences in circulating NT-proBNP levels depending on appearance of heart failure during 3 years were significant. Medians of circulating NT-proBNP levels in patients without heart failure and patients with heart failure were 5.68 (3.21-9.65) pg/ml and 27.09 (21.7-29.59) pg/ml (р<0,001). NT-proBNP positively correlated with ejection fraction of left ventricle (r = -0,503, р = 0,024). In multivariate logistic regression circulating NT-proBNP independently predicted cumulative cardiovascular events (odds ratio = 1,179; 95% CI = 1,043-1,334; р = 0.008) within 3 years of observation period. Conclusion: During 3 years after treatment of Hodgkin lymphoma 55% of patients experienced cardiovascular events. Much higher levels of circulating NT-proBNP were found in patients with heart failure in comparing with patients without heart failure. Among patients after treatment of Hodgkin lymphoma increased circulating NT-proBNP may associate with increased cumulative cardiovascular events during 3 years.